Augmented inquiry: developing ar-based media for spatial geometry in elementary schools - Rusnilawati Rusnilawati; Ardhian Fajar Rizki; Farizky Rahman; Atika Azzahro Hazima; Arief Cahyo Utomo; Jamiu Temitope Sulaimon (Prodi PGSD FKIP Universitas Islam Sultan Agung, 2026)
Mathematics learning on solid geometry topics in elementary schools still faces challenges in visualising abstract and spatial concepts. This study aimed to develop and examine the feasibility, practicality, and effectiveness of an Augmented Reality (AR) learning medium based on Inquiry Learning for fifth-grade elementary students on solid geometry material. This research employed the Research and Development (R&D) method. The research subjects consisted of two media experts, two subject-matter experts, two fifth-grade teachers, and 20 fifth-grade students at Purwosari Elementary School. Data collection instruments included expert validation questionnaires, teacher and student response questionnaires, and learning achievement tests administered through pretests and posttests. The results showed that the AR learning media was categorised as highly feasible by media experts with a percentage of 83.75% and by subject-matter experts with 88.33%. Teachers’ evaluations indicated a highly practical category with a percentage of 87.6%, while students’ responses showed a practical category with an average percentage of 75.60%. The effectiveness test revealed a significant improvement in learning outcomes, with a significance value of 0.000 (< 0.05) and an N-Gain score of 0.45, classified as moderate. The findings imply that AR-based Inquiry Learning media can serve as an innovative alternative to enhance students’ motivation, conceptual understanding, and mathematics learning outcomes in elementary schools.